2008
DOI: 10.1111/j.1464-410x.2007.07409.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting erectile function after radical retropubic prostatectomy: results from 1620 consecutive patients

Abstract: those not having a nerve-sparing procedure, neoadjuvant or adjuvant therapy within 6 months of RRP and a follow-up of < 6 months were excluded from the analyses. Erectile function was evaluated by the surgeon when possible or by an annual questionnaire. Potency was defined as erectile function sufficient for intercourse with or without a phosphodiesterase-5 inhibitor. RESULTSOf 619 men who had a bilateral and of 178 who had a unilateral nerve-sparing RRP, 72% and 53%, respectively, were potent. When stratifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 19 publications
6
73
0
3
Order By: Relevance
“…23 As shown in several other studies, patients who had undergone nerve-sparing RP have a greater chance to regain sexual function than patients who had undergone non-nerve-sparing RP. 9,10,24 However, even 1 year after nerve-sparing RP, 66% of patients had a severe form of ED, 27% of patients had regained at least some degree of EF and only 7% of patients had regained full EF. Thus, postsurgical improvement of EF does not mean a full convalescence of presurgical EF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 As shown in several other studies, patients who had undergone nerve-sparing RP have a greater chance to regain sexual function than patients who had undergone non-nerve-sparing RP. 9,10,24 However, even 1 year after nerve-sparing RP, 66% of patients had a severe form of ED, 27% of patients had regained at least some degree of EF and only 7% of patients had regained full EF. Thus, postsurgical improvement of EF does not mean a full convalescence of presurgical EF.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Thus, we expect significantly better sexual functioning in patients who had undergone nerve-sparing vs non-nerve-sparing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several trials have indicated that the best postoperative potency rates are obtained in the younger patient population. [11][12][13][14] Younger patients are more likely to have better preoperative erectile function and to be more interested in sexual recovery after surgery. [11][12][13][14] Patients between ages 40 years and 49 years reported rates of erectile function recovery as high as 92%.…”
Section: Patient and Partner Agementioning
confidence: 99%
“…[11][12][13][14] Younger patients are more likely to have better preoperative erectile function and to be more interested in sexual recovery after surgery. [11][12][13][14] Patients between ages 40 years and 49 years reported rates of erectile function recovery as high as 92%. 13 In addition to patient age, it recently was demonstrated that a difference in age between a patient and their partner is associated linearly with better sexual outcome after RP.…”
Section: Patient and Partner Agementioning
confidence: 99%
See 1 more Smart Citation